Hyperosmolar Tears Induce Functional and Structural Alterations of Corneal Nerves: Electrophysiological and Anatomical Evidence Toward Neurotoxicity - Hirata, Harumitsu (Invest Ophthalmol Vis Sci, 2015)
PURPOSE: In an effort to elucidate possible neural mechanisms underlying diminished tearing in dry eye disease, this study sought to determine if hyperosmolar tears, a ubiquitous sign of dry eye disease, produce functional changes in corneal nerve responses to drying of the cornea and if these changes correlate with alterations in corneal nerve morphology. METHODS: In vivo extracellular electrophysiological recordings were performed in rat trigeminal ganglion neurons that innervated the cornea before, and up to 3 hours after, the ocular application of continuous hyperosmolar tears or artificial tears. In corollary experiments, immunohistochemical staining was performed to compare corneal nerve morphology in control and in eyes treated with hyperosmolar solutions. RESULTS: Our previous studies identified a population of corneal afferents, dry-sensitive neurons that are strongly excited by corneal dessication (“dry response”), a response thought to trigger the lacrimation reflex. In the present study, we found that the dry responses of corneal dry-sensitive neurons were depressed or even completely abolished by hyperosmolar tears in a time- (30 minutes to 3 hours) and dose (450- to 1000-mOsm solutions)-dependent manner. Furthermore, eyes treated with hyperosmolar tears for 3 hours contained large numbers of morphologically abnormal (granular, fragmented, or prominently beaded) subbasal nerves that appeared to be undergoing degeneration. CONCLUSIONS: These results demonstrate that tear hyperosmolarity, considered to be a “core” mechanism of dry eye disease, significantly decreases physiological sensitivity and morphologic integrity of the corneal nerves important in tear production. These alterations might contribute to the diminished tearing seen clinically in dry eye patients.